Palestrina and the German romantic imagination : interpreting historicism in nineteenth-century music - Garratt, James, 1974- (Musical performance and reception., 2002)
James Garratt explores the revival of sixteenth-century music in nineteenth-century Germany, focusing on the reception of Palestrina by critics, historians, performers and composers. Of relevance to scholars, students and devotees of nineteenth-century music, and those interested in nineteenth-century culture, art, architecture, literature and aesthetics, and the early music revival.